Preparation and application of rifamycin-capped (3-(2-O-β- cyclodextrin)-2-hydroxypropoxy)-propylsilyl-appended silica particles as chiral stationary phase for high-performance liquid chromatography - Zhao, J. (2014)
10.1016/j.talanta.2010.08.031